Peran Masyarakat Dalam Penghijauan Guna Mengembangkan Kampung Tangguh di Dusun Bunut Kidul Desa Asrikaton Kecamatan Pakis - Rafika Sukma, Wanda; Galuh Eka Putri, Diestya; Jaelani, Ali Ridho; Ma'rifah, Nia Zairotul (Unity Academy, 2024)
Greening as a form of awareness of the environment that needs to be intensified starts from the microenvironment first. The movement of greening plants consisting of Red Shoots, Rombusa, and Croton (Codiaeum variegatum) Cuttings spread the community and students of Asrikaton 1 elementary school. This activity aims to make the community more aware of the current environmental conditions, reduce global warming, and make the village more beautiful. The method used is the Descriptive research method by making observations directly in the hamlet of Bunut Kidul. RT 1 is our choice to do greening because RT 1 does not include Kampung Tangguh in terms of greening is still lacking. Therefore, this activity is focused on developing resilient villages in RT 1 Bunut Kidul Hamlet. The provision of Red Shoots, Rombusa plants, and also Croton (Codiaeum variegatum) Cuttings is distributed thoroughly to the residents of RT 1, hopefully, residents will be more aware of the importance of greening and its benefits for the environment.